(3GdLRA GdKGfjs - (3YGeQ(B, (3TbQs; (3Gjef GdTfWj(B, s ((3YeGf(B:s (3OGQ GdHOGjI fGTQhf(B,s, 2005)
(3GdLQO h LQO GdCUhd GdKGHJI , LQO GdGUhd GdeJOGhdI , LQO GdMSGHGJ GdhgejI , LQO GdNUhe GdeJOGhdI , CKQ GdJShjGJ GdLQOjI Ydi bGFeI GdONd dGh GdeQcR GdeGdj , GdOaGJQ GdeSGYOI h GdWQb GdeMGSHjI h GdMSGHGJ GdeGdjI (B.s
Keywords: (3GdeMGSHIs; (3JObjb GdMSGHGJs